The anti-inflammatory effects of an ethanolic extract of the rhizome of Atractylodes lancea, involves Akt/NF-κB signaling pathway inhibition. (15th September 2021) - Hossen, Muhammad Jahangir; Amin, Aftab; Fu, Xiu-Qiong; Chou, Ji-Yao; Wu, Jia-Ying; Wang, Xiao-Qi; Chen, Ying-Jie; Wu, Ying; Li, Junkui; Yin, Cheng-Le; Liang, Chun; Chou, Gui-Xin; et al.
Abstract: Ethnopharmacological relevance: The dried rhizome of Atractylodes lancea (Thumb.) DC. (Compositae) has been prescribed in folk medicine for the management of various inflammatory conditions such as rheumatic diseases, gastritis and hepatitis. However, the molecular mechanisms underlying the beneficial properties of this herb remain elusive. Aim of the study: In this study, we investigated the anti-gastritis activities of Al-EE (an ethanolic extract of the herb) and explored the mechanism of action. Materials and methods: An ethanolic extract of the Atractylodes lancea (Thumb.) DC. (Compositae) rhizome, Al-EE, was prepared with ethanol (95%) and quality controlled using HPLC analysis. To determine the in vivo effects of this extract, we utilised a HCl/EtOH-induced gastritis rat model. In vitro assays were carried out using a lipopolysaccharide (LPS)-stimulated RAW 264.7 macrophage cell model. MTT assays were used to examine cell viability, while Griess assays were carried out to measure nitric oxide (NO) production. Messenger RNA expression was examined by real-time PCR. Prostaglandin E2 (PGE2 ) production was examined using ELISA assays. To examine protein expression and enzymatic activities, we employed western blot analysis. Nuclear transcription factor (NF)-κB activity was determined by Luciferase reporter assays. Results: The content of atractylenolide (AT)-1 and AT-2 in Al-EE was 0.45% and 5.07% (w/w), respectively (Supplementary Fig. 1). Al-EE treatment suppressed the production of NO and PGE2, reduced the mRNA expression of inducible NO synthase (iNOS), cyclooxygenase (COX)-2 and tumor necrosis factor (TNF)-α, while also reducing the protein levels of iNOS and COX-2 in RAW264.7 macrophage cells. Furthermore, Al-EE inhibited the nuclear protein levels of NF-κB (p65) and NF-κB-driven luciferase reporter gene activity in RAW264.7 macrophage cells. Critically, intra-gastric injection of Al-EE (25 mg/kg) attenuated HCl/EtOH-induced gastric damage in SD rats, while the phosphorylation of Akt and IκBα was suppressed by Al-EE in vitro and in vivo. Conclusion: In summary, Al-EE has significant anti-gastritis effects in vivo and in vitro, which can be associated with the inhibition of the Akt/IκBα/NF-κB signalling pathway. This mechanistic finding provides a pharmacological basis for the use of the A. lancea rhizome in the clinical treatment of various inflammatory conditions. Graphical abstract: Image 1